Macroeconomic Policy at a Turning Point: 25 Years of EU Macroeconomic Dialogue - Willi Koll; Wolfgang Merz (Intereconomics, 2024)
This year marks the 25th anniversary of the EU's Macroeconomic Dialogue (MED). Since entering its third decade, the MED has already faced two massive crises: the COVID-19 pandemic and the surge in energy prices. Yet European economic policymakers continue to face multiple macro-structural challenges that will also have an impact on the future work of the MED. This article explores the role of the MED during the two recent crises and considers its evolving responsibilities, particularly in light of the EU's goal of climate neutrality.
Keywords: E61; Q43; 330; Development; Economic policy; Climate policy; EU countries; Entwicklung; Wirtschaftspolitik; Klimapolitik; EU-Staaten